Acculturation of knowledge management initiative in commercial banks: the case of Malaysia - Hafizi M. Ali; Zawiyah M. Yusof (Penerbit Universiti Kebangsaan Malaysia, 2012)
Banks merger and financial liberalization has urged that banks’ operation to be based on knowledge. It is deem crucial to identify the adoption of knowledge management initiative in Malaysian commercial banks particularly on Procurement and Empowerment of knowledge; Training and Mentorship; Communication; and Incentives. A survey employing questionnaires was carried out involving all 10 domestic commercial banks focussing on Human Resource Management units. Procurement and empowerment of knowledge (four aspects), training and mentorship (six aspects), communication (three aspects), and incentives (two aspects) were examined. It is evident that knowledge management practices do exist in all of the investigated aspects. The study reveals that banks do procure and utilise knowledge from their industrial associations, competitors, customers, and suppliers and also encourage staff to pursue education by giving incentives such as reimburse the fees for job-related courses. With respect to communication, written documents such as training manuals, job procedures and practices, and articles depicting organizational knowledge are addressed. In addition, financial and non-financial incentives are also practiced which indicate that incentives are also within the concern. It is believed, this study would motivate banks in Malaysia to acknowledge the knowledge management initiative as a new activity to embark on.